Supervision of Primary and Secondary Education : A Five-Country Comparison - Mahfooz, Sara Bin; Hovde, Kate (World Bank, Washington, DC, 2012)
At the request of the Government of Poland which is reforming its educational system, the World Bank conducted a review of how five high performing countries in the education sector provide supervision and support to their schools. England, Finland, New Zealand, the Netherlands, and the Republic of Korea approach supervision and support to schools and teachers in a variety of ways; there is no single right way and their decisions take into account the overall organization of their education systems. A common theme to school supervision in all five countries is that schools are required to perform self assessments. The criteria for supervision extend beyond issues of regulatory compliance into questions about the quality of school processes, context and outcomes for students. All systems include elements of both accountability and support.